Interdimensional relations and yield of jatropha (Jatropha curcas L.) in silvopastoral system - Fey, Rubens; Malavasi, Ubirajara Contro; Malavasi, Marlene Matos; Schulz, Deisinara Giane; Dranski, João Alexandre Lopes (Semina: Ciências Agrárias, 2014)
Plant morphometric variables are used to estimate interdimensional relations, and their analysis is important to obtain information on the plant's stability, vitality, and yield. The aim of this study was to determine the morphometric variables, interdimensional relations, and the yield of jatropha grown in a silvopastoral system. Forty-five trees were measured for three years following cultivation in Latossolo, West Paraná. The characteristics under analysis were as follows: stem diameter, height, crown diameter, crown length, crown area, crown proportion, slenderness ratio, salience index, coverage index, crown formation, number of branches, and yield. The assessments were carried out between January 2011 and July 2011. Stem diameter showed the best correlation with jatropha crop yield. For the same variable, significant regression models were obtained for the following: plant height, crown diameter, slenderness ratio, and coverage index.